2011
DOI: 10.1002/jcu.20815
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the breast from extramammary malignancies—sonographic features

Abstract: Metastatic tumors in the breast have a wide range of sonographic appearances, with some resembling benign lesions. Any newly developed mass in a patient with a known history of extramammary malignancy, even with a probably benign US appearance, should undergo biopsy for pathologic confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Metastasis may show single or multiple and unilateral or bilateral lesions. 11,14 In this study, a single and unilateral breast mass from non-breast metastatic disease are more prevalent and masses are more common than diffused infiltrative lesions. The mass was located in the left breast in most cases.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Metastasis may show single or multiple and unilateral or bilateral lesions. 11,14 In this study, a single and unilateral breast mass from non-breast metastatic disease are more prevalent and masses are more common than diffused infiltrative lesions. The mass was located in the left breast in most cases.…”
mentioning
confidence: 90%
“…The common manifestations of ultrasonography were round to oval shaped, well-defined hypoechoic solid masses. 11,[14][15][16][17][18] Some of our results were different. The sonogram of breast masses is more common with irregular shape and unclear boundaries (13/14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The common symptoms in all reported cases of breast metastases, including from gastric cancer, are a non-tender palpable mass, diffuse edema of the skin, or erythema. However the radiologic features of secondary breast malignancies tend to indicate a benign tumor [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To date, reports have indicated that intramammary metastases in general are often round, firm, and not accompanied by pain. Distinguishing intramammary metastases from benign tumors (e.g., fibroadenoma, hamartoma, and phyllodes tumors) and breast cancer (e.g., medullary cancer, mucinous carcinoma, and solid tubular carcinoma) is clinically problematic because of similar form and properties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%